Selection of general fitness development exercises for first year female students of Duy Tan University (Vietnam) - Hung, Nguyen Xuan; Khoa, Nguyen Huu Anh (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
The aim of this study was to select and evaluate exercises designed to develop general fitness for first-year female students. A randomized controlled trial design (parallel design) was employed. The research methods included document analysis and synthesis, interviews, pedagogical observation, pedagogical examination, pedagogical experiments, and statistical analysis. A total of 200 first-year female students enrolled in the Physical Education Program at Duy Tan University in Da Nang City participated. They were divided into two groups by random drawing by class: the experimental group (N=100) and the control group (N=100). The experimental group followed the Physical Education program at Duy Tan University with the addition of the selected exercises and modifications, while the control group followed the standard General Physical Education program. The researcher selected 28 exercises categorized into two groups: Group 1 (exercises with limited movement, 23 exercises) and Group 2 (exercises measuring each part of movement, 5 exercises). The results showed significant improvements in all tested fitness parameters for the experimental group compared to the control group (p<0.05). Additionally, the achievement growth rate in all tests assessing general fitness was higher for the experimental group (p<0.05). The initial application and evaluation of these exercises demonstrated high efficiency in improving the general fitness of the first-year female students.